Mutualistic Networks - Bascompte, Jordi, 1967- (Book collections on Project MUSE., 2014)
Mutualistic interactions among plants and animals have played a paramount role in shaping biodiversity. Yet the majority of studies on mutualistic interactions have involved only a few species, as opposed to broader mutual connections between communities of organisms. Mutualistic Networks is the first book to comprehensively explore this burgeoning field. Integrating different approaches, from the statistical description of network structures to the development of new analytical frameworks, Jordi Bascompte and Pedro Jordano describe the architecture of these mutualistic networks and show thei.